Finite‐time disturbance observer‐based trajectory tracking control for quadrotor unmanned aerial vehicle with obstacle avoidance. (12th July 2022) - Li, Bo; Zhang, Haichao; Niu, Yuxiao; Ran, Dechao; Xiao, Bing
Abstract : This paper investigates the problem of trajectory tracking control for quadrotor unmanned aerial vehicle (UAV) in the presence of dynamic obstacles and external disturbance forces/torques. More specifically, two new sliding mode disturbance observers are firstly designed to estimate the external disturbances, in which the observation errors can converge to zero in finite time. Furthermore, utilizing the observation information, a new sliding mode surface‐like variable‐based position tracking control scheme and a novel nonsingular terminal sliding mode‐based attitude synchronization control scheme are developed to drive the UAV tracking the reference trajectory with obstacle avoiding. Moreover, the tracking errors of the close‐loop control system can converge to zero within finite time by the analyses of Lyapunov methodology. Finally, the numerical simulation results are presented to illustrate the effectiveness of the proposed control schemes.